PENERAPAN REGRESI ROBUST ESTIMASI-S DENGAN FUNGSI PEMBOBOT TUKEY BISQUARE DAN WELSCH PADA KASUS DATA IPM DI PROVINSI PAPUA TAHUN 2021 - Nurcahyani, Nita; Pratikno, Budi; Supriyanto, Supriyanto (Universitas Jenderal Soedirman, 2022)
ABSTRACT. The research studied the robust regression estimation-S on Tukey-Bisquare and Welsch weighting function. Due to the data contains outliers, we therefore used robust regression to handle outliers. The purpose is to find the best model between the Tukey Bisquare or Welsch. The mean square error (MSE) and adjusted R^2 is then used. The simulation data is a human development index (HDI) in Papua in 2021. The result showed that the robust regression model on the S-estimation between Tukey Bisquare and Welsch are similar (close). However, the adjusted R^2 weighting function Welsch is greater than the Tukey Bisquare, and the MSE of the Welsch is smaller than the Tukey Bisquare, so we recommended the robust S-estimation Welsch is a little better.Keywords: Outlier, robust, estimate-S, Tukey Bisquare weighting function, Welsch weighting function. ABSTRAK. Penelitian ini membahas penerapan model estimasi parameter regresi robust estimasi S fungsi pembobot Tukey-Bisquare dan Welsch pada kasus data IPM tahun 2021. Karena data memuat outlier, maka model regresi robust dipertimbangkan sebagai model yang dapat mengatasi outlier. Tujuan penelitian ini adalah mencari model terbaik antara fungsi pembobot Tukey Bisquare dengan Welsch berdasarkan kriteria mean square error (MSE) dan adjusted R^2. Hasil riset menunjukan bahwa estimasi regresi robust estimasi-S dengan fungsi pembobot Tukey Bisquare dan Welsch serupa atau cenderung sama. Namun jika dilihat dari nilainya, adjusted R^2 fungsi pembobot Welsch lebih besar dari pembobot Tukey Bisquare, dan MSE fungsi pembobot Welsch lebih kecil dari pembobot Tukey Bisquare, karena itu regresi robust estimasi-S dengan fungsi pembobot Welsch lebih di rekomendasikanKata Kunci: Outlier, regresi robust, Estimasi-S, fungsi pembobot Tukey Bisquare, fungsi pembobot Welsch.